2015
DOI: 10.11622/smedj.2014170
|View full text |Cite
|
Sign up to set email alerts
|

Insulin therapy refusal among type II diabetes mellitus patients in Kubang Pasu district, Kedah, Malaysia

Abstract: INTRODUCTION Diabetes mellitus is a rising non-communicable disease in Malaysia. Insulin therapy refusal is a challenge for healthcare providers, as it results in delayed insulin initiation. This study was conducted to determine the prevalence of insulin therapy refusal and its associated factors. METHODSThis cross-sectional study was conducted at seven public health clinics in Kubang Pasu district of Kedah, Malaysia, from March to October 2012. A newly developed and validated questionnaire was used and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 5 publications
(11 reference statements)
10
30
8
1
Order By: Relevance
“…Unlike other studies, we found that participants with tertiary education were less willing to commence insulin compared to those with less education [9,23]. Participants with better educational backgrounds are expected to be more knowledgeable about diabetes and might therefore be more likely to accept the need to commence insulin.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Unlike other studies, we found that participants with tertiary education were less willing to commence insulin compared to those with less education [9,23]. Participants with better educational backgrounds are expected to be more knowledgeable about diabetes and might therefore be more likely to accept the need to commence insulin.…”
Section: Discussioncontrasting
confidence: 89%
“…The unwillingness to commence insulin therapy in this study was higher than that reported in the USA (28 and 33%) [20,21]. However, it is lower than those reported in different regions of Asia with the highest prevalence in Iran (77%), Malaysia (74.2%, 50.7%) and Singapore (70.6%) [9,23,24,31]. The differences in prevalence of unwillingness to begin insulin and the attitudes towards insulin therapy between countries may be related to cultural and health care system factors.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations